Identifikasi Protein dan Seleksi Isolat Trypanosoma evansi Bersifat Imunogenik untuk Kandidat Pengembangan Imunoasai - Subekti, Didik T.; Yuniarto, Ichwan (Perhimpunan Biologi Indonesia, 2018)
ABSTRACTSurra is a parasitic disease caused by T. evansi and causing high economic losses in Indonesia. Some isolates have been isolated from several areas experiencing outbreaks of Surra in Indonesia. The isolates have been reported to have a diversity of protein profiles based on SDS PAGE (sodium dodecyl sulphate polyacrilamide gel electrophoresis). The research aims to identify immunogenic protein from each isolate and make the selection of T. evansi isolates which is potential as a source of antigens for immunoassay development. Each isolates were obtained to be purified from blood and then the protein was isolated. The proteins were run onto polyacrylamide gel electrophoresis and visualized by Coomassie blue. Another electrophoresis results were transferred onto a nitrocellulose membrane for immunoblotting. The results showed that the immunogenic proteins that consistently detected among nine T. evansi isolates of Indonesia are 100, 90, 85, 76-80, 70, 65, 55, 49-52, 44-46, 40, 34-36, 31 -33 kDa. Among the nine T. evansi isolates, N372 isolate was selected as a candidate for immunoasay development, especially ELISA. Immunogenic proteins were specifically found on the N372 isolate are 85, 70, 65, 49-52, 44-46, 34-36, 31-33, 24-28, 15-20 kDa.Keywords : Trypanosoma evansi, immunoblotting, protein profiles, immunogenic protein